Gender Harassment Persists in Medical Training - Carolina Vogel; Theresa Rohr-Kirchgraber (Mary Ann Liebert, 2020)
Medical students start their career with enthusiasm for a profession that emphasizes caring for others so as to promote health, treat injury, and prevent disease. The profession of medicine selects those who have demonstrated compassion, knowledge, and leadership. As students enter the profession, many possess a certain naivet? with the expectation for equity. After a few encounters of her own, one of our authors wondered whether the statistic that female medical students are ?220% greater to experience harassment in medical education from faculty, staff, and patients was true and sought to determine whether her experience was unique. Unfortunately, with just a quick Instagram post, she received numerous messages from peers indicating that gender harassment is all too common.